Cambodia$1 (Bs Curse : s The Modern History of a Troubled Land - Brinkley, Joel , 1952- (New York : PublicAffairs, 2011)
Nobel Prize winning reporter Joel Brinkley illuminates the country, its people, and the deep historical roots of its modern-day behavior
Includes bibliographical references (p. 367) and index
Keywords: Pol, Pot,1925 -1998; Democracy -- Cambodia; Social change -- Cambodia; Cambodia -- History -- 1979-; Cambodia -- Politics and government -- 1979-; Cambodia -- Social conditions -- 21st century